The effect of weight training dumbbell swing uses the opposite side to the skill forehand topspin and backhand topspin" "Pade Angen Mataram Table Tennis Athlete in 2024 - Fahriansyah fahriansyah (JOETAL: Journal of Education, Teaching and Learning, 2024)
This research aims to find out the effect of weight training dumbbell swing using the opposite side to the skill forehand topspin and backhand topspin for the 2024 Pade Angen Mataram Table Tennis Athlete. This research is experimental research, the research design used one group pre-test-post test design where in this research there was no comparison group. The population used in this research is table tennis athletes Pade Angen Mataram Table Tennis Athletes for 2024, totaling 12 players. The instrument used is a test forehand topspin dan backhand topspin. Data analysis in this study used the SPSS test. The research results were obtained there is an influence of weight training dumbbell swing use the opposite side to the skill forehand topspin for Pade Angen Mataram Table Tennis Athletes in 2024, with t value count 12,429 > ttable (0.05)(10) 2.262, a significance value of 0.000 < 0.05, and a percentage increase of 19.33%, so Ha is accepted. There is an influence of weight training dumbbell swing use the opposite side to the skill backhand topspin for Pade Angen Mataram Table Tennis Athletes in 2024, with t valuecount 8,820> ttable(0.05) (10) 2.262, a significance value of 0.000<0.05, and a percentage increase of 18.03%, so Ha is accepted. So it can be concluded that there is an influence of weight training dumbbell swing using the opposite side to the skill forehand topspin and backhand topspin for the 2024 Pade Angen Mataram Table Tennis Athlete.